College attainment, income inequality, and economic security: A simulation exercise - Brad Hershbein; Melissa Schettini Kearney; Luke W. Pardue (W.E. Upjohn Institute for Employment Research, 2020)
We conduct an empirical simulation exercise that gauges the plausible impact of increased rates of college attainment on a variety of measures of income inequality and economic insecurity. Using two different methodological approaches-a distributional approach and a causal parameter approach-we find that increased rates of bachelor's and associate degree attainment would meaningfully increase economic security for lower-income individuals, reduce poverty and near-poverty, and shrink gaps between the 90th and lower percentiles of the earnings distribution. However, increases in college attainment would not significantly reduce inequality at the very top of the distribution.
Keywords: I24; I26; I30; J21; J24; J31; 330; education; college attainment; income inequality; earnings distribution; economic security poverty